Health behaviors of pregnant women attending antenatal classes - Justyna Krzepota (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2013)
The aim of this study was to analyse health behavior, taking into account the following aspects: proper nutritional habits (PNH), preventive behaviors (PB), positive thinking (PT) and health practices (HP) in the light of general index of intensity of health behaviors (GIIHB) of pregnant women participating in antenatal classes in Szczecin. Juczyński’s (2001) Health Behavior (HBI) Inventory constitutes the methodological basis for this investigation. Among examined respondents participating in prenatal school activities a high health behaviors indicator was stated in nearly half of them (49.0%). Unfortunately, among the rest of examined pregnant women health behaviors were on the average (37.4%) or low level (13.6%). None of the above categories of health behaviours obtained remarkably higher point values. Therefore, it can be stated that there is a necessity to promote preventive activities to spread information concerning healthy eating habits and to recommend advantages resulting from health behaviors.